A note on finite-time and fixed-time stability. (September 2016) - Lu, Wenlian; Liu, Xiwei; Chen, Tianping
Abstract: In this letter, by discussing t ̇ ( V ) = μ − 1 ( V ), we provide a general approach to reveal the essence of finite-time stability and fixed-time convergence for the system V ̇ ( t ) = μ ( V ( t ) ) . Thus, we derive some conditions for finite-time and fixed-time convergence. As applications, we propose schemes to achieve finite-time and fixed-time synchronization in complex networked systems.